ANALISIS YURIDIS PENGATURAN HARTA SYIRKAH DALAM PERKAWINAN ISLAM DI INDONESIA - NIM. A1012181109, M TAUFIQ KUSUMA PUTRA (Jurnal Fatwa Hukum, 2025)
Abstract This study aims to analyze the regulation of joint property (harta syirkah) in Islamic marriage in Indonesia, focusing on the alignment between Islamic law and positive law in Indonesia regarding joint ownership between husband and wife. Harta syirkah, defined as partnership in property ownership, is regulated in both Islamic law and the Compilation of Islamic Law (KHI), but its application faces challenges, particularly in the division of property during divorce or after death. This research employs a normative juridical method with an analytical approach to the applicable legal provisions and previous research findings. The discussion includes the concept of harta syirkah in Islamic law, the regulation of harta syirkah in the KHI, challenges in its implementation, and potential solutions to improve its effectiveness. The research findings indicate that although the regulation of harta syirkah is addressed by both Islamic law and positive law in Indonesia, its implementation is hindered by a lack of public understanding, inconsistencies between Islamic law and positive law, and limitations in the religious court system in handling disputes over harta syirkah. As solutions, this study recommends enhanced legal education and outreach, strengthening the religious court system, and promoting clear marital agreements to prevent future disputes. This research is expected to contribute to improving the management of harta syirkah in Islamic marriages in Indonesia. Keywords: Harta Syirkah, Islamic Marriage, Compilation of Islamic Law, Property Management, Property Division Abstrak Penelitian ini bertujuan untuk menganalisis pengaturan harta syirkah dalam perkawinan Islam di Indonesia, dengan fokus pada kesesuaian antara hukum Islam dan hukum positif Indonesia dalam mengatur harta bersama antara suami dan istri. Harta syirkah, yang diartikan sebagai kemitraan dalam kepemilikan harta, diatur dalam hukum Islam dan Kompilasi Hukum Islam (KHI), namun penerapannya masih menemui kendala di lapangan, terutama dalam hal pembagian harta saat perceraian atau kematian. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan analisis terhadap aturan-aturan hukum yang berlaku serta hasil penelitian terdahulu. Pembahasan dalam penelitian ini meliputi konsep harta syirkah dalam hukum Islam, pengaturan harta syirkah dalam KHI, kendala dalam implementasinya, dan solusi yang dapat diupayakan untuk meningkatkan efektivitas pengaturan tersebut. Hasil penelitian menunjukkan bahwa meskipun pengaturan harta syirkah sudah diatur oleh hukum Islam dan hukum positif Indonesia, implementasinya masih terbentur oleh kurangnya pemahaman masyarakat, ketidakselarasan antara hukum Islam dan hukum positif, serta keterbatasan sistem pengadilan agama dalam menangani sengketa harta syirkah. Sebagai solusi, penelitian ini merekomendasikan peningkatan sosialisasi dan pendidikan hukum, penguatan sistem pengadilan agama, serta promosi perjanjian perkawinan yang jelas untuk mencegah sengketa di masa depan. Penelitian ini diharapkan dapat memberikan kontribusi dalam memperbaiki pengelolaan harta syirkah dalam perkawinan Islam di Indonesia. Kata Kunci: Harta Syirkah, Perkawinan Islam, Kompilasi Hukum Islam, Pengelolaan Harta, Pembagian Harta